Tazkiyatun Nafs dalam Mengembalikan Fitrah Manusia Modern - Ahmad Zainal Anbiya (Islamic Counseling: Jurnal Bimbingan dan Konseling Islam, 2023)
Religious guidance, through understanding modern human issues and teachings such as Sufism, seeks to provide pragmatic goals in forming mental health to foster good morals in modern individuals who are tainted by various worldly diseases such as hedonistic and materialistic behaviors, which reduce spiritual quality. This study used a descriptive qualitative approach by presenting an understanding of human potential and the concept of tazkiyatun nafs and related analyses. Tazkiyatun Nafs is one of the concepts that discuss the first step for Sufis to cleanse themselves from all sins through three core stages: takhalli, tahalli, and tajalli. This study concludes that these three stages are the beginning and end for Sufis in their efforts to obtain Allah's grace in the form of divine consciousness to enhance and protect their personal qualities to become insan al kamil, a strong figure who is not easily discouraged by their efforts, even if they are not successful.